Caffeine Ingestion among Athletes Based on Safe Dose Daily Allowance in Malaysia - Musa, Sitti Junaina; Ghazali, Ahmad Rohi; Mohamad Fauzi, Nor Farah; Abd Rahman, Abdul Hadi; Izham Mohamad, Mohd; Shanita Safii, Nik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aims to investigate the category of caffeinated beverages ingested and caffeine ingestion level among athletes based on safe dose daily allowance. A cross-sectional study was conducted among 236 athletes using validated Caffeine Consumption Questionnaire (CCQ) to estimate the caffeine intake among athletes. The findings revealed a high prevalence (69.1%) of caffeine consumption exceeding the recommended daily allowance was observed among the athletes. Among the various Caffeinated Beverage (CB) categories, Coffee Drink (CD) showed the highest median and interquartile range of caffeine intake 243.0 mg (0–919.5 mg). There was a significant correlation (p<0.05) between types of CB Energy Drink (ED) with pre-event (r=0.280), during-event (r=0.447), post-event (r=0.291). Energy Gel (EG) with pre-event (r=0.139), during-event (r=0.498), post-event (r=0.170). Soft Drink (SD) with pre-event (r=0.328), during-event (r=0.228), post-event (r=0.304). CD with pre-event (r=0.534), during-event (r=0.132), post-event (r=0.240). Tea Drink (TD) with pre-event (r=0.148), post-event (r=0.190). Cocoa Drink (CocD) with pre-event (r=0.158), post-event (r=0.137). A significant association (p<0.05) was observed between the range dose allowance of caffeine intake and the timing of ingestion during sports events. The daily caffeine consumption among athletes in Malaysia exceeds the recommended safe dose. Therefore, it is essential to monitor, track and regulate the intake of caffeine-containing beverages by implementing clear guidelines and promoting awareness of caffeine-related facts. This approach aims to prevent potential adverse health effects while ensuring athletes can still harness its performance-enhancing benefits.